Effect of elevation and latitude on spring phenology of Rhododendron at Kanchenjunga conservation area, East Nepal - Ranjitkar S (Nepal Journals Online, 2013)
Mountainous terrain in East corner of Nepal is good location for phenological studies. Spring phenology in Rhododendron arboreum Sm. was monitored around Ghunsa river valley in Kanchenjunga Conservation Area of Nepal. Observations were carried our following the crown density method; flowering events of the selected species were recorded in 15-days interval. Flowering activity including duration of flowering and synchrony were determined. In addition, expected difference in flower onset time in two consecutive monitoring plots was determined. Elevation, latitude and longitude were regressed against flower onset to determine effect of each variable on flower onset. Delay in flower onset with rise in elevation, North latitude and West longitude was found in the results of the regression. Full bloom phase was found highly synchronized throughout the elevation gradient with contraction of flowering duration. High synchrony also indicates that the reproductive timing might plastic enough to cope with short-term change in environment.